Tingkat Kepuasan Pasien Terhadap SIANTER (Sistem Informasi Antrian Terintegrasi) di UPTD Puskesmas Kresek Kabupaten Tangerang - Fiqih Nurhidayah; Puteri Fannya; Laela Indawati; Dina Sonia (Pusat Riset dan Inovasi Nasional, 2024)
Patient satisfaction is an assessment of whether or not the quality of health services for patients is good. One of the influences on the level of patient satisfaction is the queue, to prevent chaos in the waiting room caused by queues, a queue system is created in a health service. This study aims to determine the level of patient satisfaction with SIANTER (Integrated Queuing Information System) at the Kresek Health Center. The sample in this study amounted to 106 respondents using the Non Probability Sampling technique with the consecutive sampling method. To measure the level of patient satisfaction with the queuing system, the End User Computing Statistics (EUCS) method is used which consists of five dimensions of content, accuracy, format, ease of use, and timeline. The data collection technique used in the study was by filling in the patients themselves with the instrument used was a questionnaire. The results showed that (81.1%) were dissatisfied, and 20 respondents (18.9%) were satisfied. This study concluded that there are still many patients who are dissatisfied with the use of the SIANTER machine (Integrated Queuing Information System) at the Kresek Health Center.